2021
DOI: 10.1177/1558944720988080
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Clinical Results of Carpal Tunnel Release Using Ultrasound Guidance

Abstract: Background: The purpose of this study was to determine the long-term safety and efficacy of carpal tunnel release (CTR) using ultrasound guidance in a group of patients treated by a single physician. Methods: The study group consisted of 76 consecutive CTRs performed on 47 patients between June 2017 and April 2019 for whom 1-year follow-up was available. All procedures were performed by the same operator using a single CTR technique. Outcomes included complications; Boston Carpal Tunnel Questionnaire symptom s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
65
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(68 citation statements)
references
References 40 publications
(79 reference statements)
3
65
0
Order By: Relevance
“…However, the primary purpose of this investigation was to specifically document the safety and effectiveness of office-based CTR using US guidance in our community practice. Of note, the current results are similar to those reported by Leiby et al for 76 hands in 47 patients treated in the ambulatory surgery center or hospital operating room setting with the same US-guided CTR technique [ 19 ]. Second, the follow-up data reported in the current study were obtained primarily through mailed questionnaires and only 123 of 200 hands in 88 of 140 patients provided one-year follow-up.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…However, the primary purpose of this investigation was to specifically document the safety and effectiveness of office-based CTR using US guidance in our community practice. Of note, the current results are similar to those reported by Leiby et al for 76 hands in 47 patients treated in the ambulatory surgery center or hospital operating room setting with the same US-guided CTR technique [ 19 ]. Second, the follow-up data reported in the current study were obtained primarily through mailed questionnaires and only 123 of 200 hands in 88 of 140 patients provided one-year follow-up.…”
Section: Discussionsupporting
confidence: 89%
“…To date, seven studies have documented the long-term (> one-year) safety and effectiveness of CTR using US guidance, including one prospective, randomized study demonstrating significantly faster recovery compared to mini-open CTR (mOCTR) [ 9 , 11 , 15 , 19 - 22 ]. However, none of these studies reported results from large patient cohorts (> 100 hands) treated in an office-based procedure room.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations